Trioctyl citrate plasticizer as well as preparation process and application thereof
By using Zr-Ce-TiO2/concave and concave rod-soil composite catalyst, the preparation process of trioctyl citrate is optimized, and the problems of environmental pollution and wastewater treatment costs of catalysts in traditional processes are solved, and an efficient and environmentally friendly preparation process is achieved, and the purity and esterification rate of the product are improved.
Patent Information
- Application Number
- CN202510372547.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The sulfuric acid catalyst used in the traditional trioctyl citrate preparation process is harmful to the environment and generates a large amount of wastewater during the reaction, which increases the treatment cost.
Using Zr-Ce-TiO2/concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave
The esterification rate and product purity of trioctyl citrate are improved, the generation of by-products is reduced, the catalyst has good stability and reusability, and the production cost is reduced. The process is environmentally friendly and avoids environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plasticizers, and in particular to a trioctyl citrate plasticizer and a preparation process and application thereof. Background Art
[0002] In the modern plastics industry, plasticizers are important additives and are widely used in the manufacture of plastic products such as polyvinyl chloride (PVC) and polyethylene (PE) to improve the flexibility, processability and ductility of plastics. However, traditional plasticizers such as phthalates (PAEs) are gradually being replaced by non-toxic and environmentally friendly new plasticizers due to their potential carcinogenicity and environmental pollution. Trioctyl citrate (TOC), as a non-toxic and environmentally friendly plasticizer, has received widespread attention due to its excellent cold resistance, light resistance, water resistance, good compatibility, high plasticization efficiency and low volatility.
[0003] Trioctyl citrate is usually produced by esterification reaction of citric acid and industrial octanol (2-ethylhexanol) in the presence of a catalyst and a water-carrying agent. Traditional processes often use sulfuric acid as a catalyst under vacuum conditions, but sulfuric acid catalysts are not only harmful to the environment, but also produce a large amount of wastewater during the reaction, increasing the cost of treatment.
[0004] Existing patent CN101245008A discloses a method for synthesizing trioctyl citrate, which uses citric acid and n-octanol as reactants, uses naphthalenesulfonic acid methylal as a catalyst in the ester synthesis process, and after the reaction is completed, the catalyst is filtered out from the reacted materials, and the filtrate is washed with water, washed with alkali, and distilled to obtain trioctyl citrate. The invention has the following advantages: (1) high yield, 97.5-99.6%; (2) cheap catalyst, small amount of catalyst, accounting for about 0.1-2.0% of the total weight of the reaction raw materials; (3) mild reaction conditions, short reaction time; (4) catalyst can be reused; (5) no environmental pollution, etc. Among them, naphthalenesulfonic acid methylal may be partially decomposed during the heating reaction, resulting in damage to the catalyst structure, and long-term use requires frequent addition of new catalyst.
[0005] Therefore, it is particularly important to develop an environmentally friendly and efficient preparation process of trioctyl citrate. Based on this, the present invention provides a trioctyl citrate plasticizer and its preparation process and application. Summary of the invention
[0006] The invention aims to provide a trioctyl citrate plasticizer and a preparation process and application thereof, and improve the purity and quality of the product by optimizing the preparation process.
[0007] In one aspect, the present invention provides a preparation process of trioctyl citrate plasticizer, the preparation process comprising the following steps: (1) Preparation of catalyst: Disperse attapulgite in an ethanol solution of tetrabutyl titanate and cerium nitrate, add sulfuric acid solution and zirconium hydroxide solution dropwise thereto, and add anhydrous sodium sulfate as a stabilizer, stir at 70-80°C for 20-24h, filter and wash with distilled water, then dry at 60-70°C for 3-4h, grind into powder, and calcine at 400-500°C for 3.5-4.5h to obtain a Zr-Ce-TiO2 / attapulgite composite catalyst; (2) Mix citric acid, n-octanol, a catalyst and cyclohexane, heat and reflux to react until the acid value no longer changes. After the reaction is completed, cool naturally, wash, separate the liquids, and dealcoholize under reduced pressure to obtain the product.
[0008] Furthermore, the average particle size of the attapulgite is 200-300 meshes.
[0009] Furthermore, the weight ratio of the attapulgite, tetrabutyl titanate, cerium nitrate, ethanol, sulfuric acid solution, zirconium hydroxide solution and anhydrous sodium sulfate is (20-30): (5-8): (1-2): (50-70): (8-10): (10-15): (1-2).
[0010] Furthermore, the concentration of the sulfuric acid solution is 0.5-1 mol / L, and the zirconium hydroxide solution is a saturated aqueous solution of zirconium hydroxide.
[0011] Furthermore, the weight ratio of the citric acid, n-octanol, catalyst and cyclohexane is (6-8):(12-14):(0.1-0.2):(12-14).
[0012] Furthermore, the temperature of the heating reflux reaction is 170-175° C., and the reaction time is 2-3 hours.
[0013] Furthermore, the washing is performed by washing 3-4 times at 70-80° C. with a 4% by volume sodium carbonate aqueous solution.
[0014] On the other hand, the present invention also provides the trioctyl citrate plasticizer prepared by the preparation process of the trioctyl citrate plasticizer.
[0015] On the other hand, the present invention also provides the use of the trioctyl citrate plasticizer in plastic additives.
[0016] The beneficial effects of the present invention are: In the present invention, attapulgite is used as a load, which is rich in key components such as SiO2 and Al2O3, and is combined with a specific ratio of sulfuric acid solution, a saturated aqueous solution of zirconium hydroxide and anhydrous sodium sulfate to prepare a high-efficiency catalyst Zr-Ce-TiO2 / attapulgite composite catalyst; the catalyst can not only effectively promote the esterification reaction of citric acid and n-octanol, but also has high catalytic activity and stability, so that the esterification reaction can be carried out efficiently, and by optimizing the preparation process of the catalyst, the generation of by-products is reduced, and the purity of the target product trioctyl citrate is improved.
[0017] The Zr-Ce-TiO2 / attapulgite composite catalyst proposed by the present invention, in which the ternary system forms unique acid sites and redox centers through the synergistic effect of Ti and Ce, significantly improving the catalytic activity. This synergistic catalytic effect is reflected in the esterification rate of up to 99.5% in Example 1, which is much higher than that of Comparative Example 1 (without Ti) and Comparative Example 2 (without Ce). The Ti element introduces acid sites into the system, which is conducive to the esterification reaction; while the Ce element promotes the conversion of reaction intermediates through its redox properties, thereby accelerating the rate of the esterification reaction.
[0018] In the preparation process of the catalyst of the present invention, the selection of the carrier has an important influence on the catalytic performance. The present invention selects attapulgite as the carrier, and its special pore structure and surface hydroxyl groups are conducive to the dispersion and anchoring of the active components. The catalyst prepared from attapulgite shows significant advantages in esterification rate and reusability. This is because the layered chain structure of attapulgite provides more anchoring points, so that the active components can be more evenly distributed on the carrier surface, thereby improving the catalytic efficiency.
[0019] The catalyst prepared by the present invention has good stability. The catalyst of Example 1 can still maintain an efficiency of 98.9% after 4 cycles. This is mainly attributed to the rigid skeleton of attapulgite preventing thermal collapse, the Na2SO4-ZrO2 solid solution formed by the sodium sulfate stabilizer, and the Ce 3+ / Ce 4+ The oxidation buffering effect reduces carbon deposition. These mechanisms work together to enable the catalyst to maintain high catalytic activity after long-term use.
[0020] The present invention achieves efficient esterification reaction by precisely controlling the reaction temperature, time and raw material ratio. The esterification rate obtained by the method is as high as 99.5%. After the catalyst is reused 4 times, the esterification rate can still be maintained at 98.9%, indicating that the catalyst has good stability and reusability, which helps to reduce production costs. DETAILED DESCRIPTION
[0021] The technical scheme of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the raw materials can be obtained commercially.
[0022] Example 1 This embodiment provides a preparation process of trioctyl citrate plasticizer, the steps comprising: (1) Preparation of catalyst: Take attapulgite with an average particle size of 250 mesh and disperse it in an ethanol solution of tetrabutyl titanate and cerium nitrate, add a sulfuric acid solution with a concentration of 0.75 mol / L and a saturated aqueous solution of zirconium hydroxide, and add anhydrous sodium sulfate as a stabilizer. Stir at 75°C for 22 hours, filter, wash with distilled water, and then dry at 65°C for 3.5 hours. After grinding, calcine at 460°C for 4 hours to obtain a Zr-Ce-TiO2 / attapulgite composite catalyst; The weight ratio of the attapulgite, tetrabutyl titanate, cerium nitrate, ethanol, sulfuric acid solution, zirconium hydroxide solution and anhydrous sodium sulfate is 25:6:1.5:60:9:12.5:1.5; (2) Mix citric acid, n-octanol, a catalyst and cyclohexane, heat and reflux for reaction at a temperature of 173°C for 2.5 hours until the acid value no longer changes. After the reaction is completed, cool naturally and wash three times with a 4% by volume aqueous solution of sodium carbonate at 75°C. Separate the liquids and dealcoholize under reduced pressure to obtain the product.
[0023] Wherein, the weight ratio of the citric acid, n-octanol, catalyst and cyclohexane is 7:13:0.15:13.
[0024] The acid value before and after the esterification reaction was measured according to the GB1668-95 method. In this embodiment, the esterification rate was 99.5%. After the catalyst was reused 4 times, the esterification rate could still be maintained at 98.9%.
[0025] Example 2 This embodiment provides a preparation process of trioctyl citrate plasticizer, the steps comprising: (1) Preparation of catalyst: Take attapulgite with an average particle size of 200 mesh and disperse it in an ethanol solution of tetrabutyl titanate and cerium nitrate, add 0.5 mol / L sulfuric acid solution and saturated aqueous solution of zirconium hydroxide, and add anhydrous sodium sulfate as a stabilizer, stir at 70°C for 20 h, filter and wash with distilled water, then dry at 60°C for 3 h, grind and calcine at 400°C for 3.5 h to obtain Zr-Ce-TiO2 / attapulgite composite catalyst; The weight ratio of the attapulgite, tetrabutyl titanate, cerium nitrate, ethanol, sulfuric acid solution, zirconium hydroxide solution and anhydrous sodium sulfate is 20:5:1:50:8:10:1; (2) Mix citric acid, n-octanol, a catalyst and cyclohexane, heat under reflux at a reaction temperature of 170°C for 2 hours until the acid value no longer changes. After the reaction is completed, cool naturally, wash three times with a 4% by volume aqueous solution of sodium carbonate at 70°C, separate the liquids, and dealcoholize under reduced pressure to obtain the product.
[0026] Wherein, the weight ratio of the citric acid, n-octanol, catalyst and cyclohexane is 6:12:0.1:12.
[0027] The acid value before and after the esterification reaction was measured according to the GB1668-95 method. In this embodiment, the esterification rate was 99.3%. After the catalyst was reused 4 times, the esterification rate could still be maintained at 98.6%.
[0028] Example 3 This embodiment provides a preparation process of trioctyl citrate plasticizer, the steps comprising: (1) Preparation of catalyst: Take attapulgite with an average particle size of 300 mesh and disperse it in an ethanol solution of tetrabutyl titanate and cerium nitrate, add 1 mol / L sulfuric acid solution and saturated aqueous zirconium hydroxide solution, and add anhydrous sodium sulfate as a stabilizer, stir at 80°C for 24 hours, filter and wash with distilled water, then dry at 70°C for 4 hours, grind and calcine at 500°C for 4.5 hours to obtain Zr-Ce-TiO2 / attapulgite composite catalyst; The weight ratio of the attapulgite, tetrabutyl titanate, cerium nitrate, ethanol, sulfuric acid solution, zirconium hydroxide solution and anhydrous sodium sulfate is 30:8:2:70:10:15:2; (2) Mix citric acid, n-octanol, a catalyst and cyclohexane, heat under reflux at a reaction temperature of 175°C for 3 hours until the acid value no longer changes. After the reaction is completed, cool naturally, wash four times with a 4% by volume sodium carbonate aqueous solution at 80°C, separate the liquids, and dealcoholize under reduced pressure to obtain the product.
[0029] Wherein, the weight ratio of the citric acid, n-octanol, catalyst and cyclohexane is 8:14:0.2:14.
[0030] The acid value before and after the esterification reaction was measured according to the GB1668-95 method. In this embodiment, the esterification rate was 99.4%. After the catalyst was reused 4 times, the esterification rate could still be maintained at 98.7%.
[0031] Example 4 This embodiment provides a preparation process of trioctyl citrate plasticizer, the steps comprising: (1) Preparation of catalyst: Take attapulgite with an average particle size of 200 mesh and disperse it in an ethanol solution of tetrabutyl titanate and cerium nitrate, add 1 mol / L sulfuric acid solution and saturated aqueous zirconium hydroxide solution, and add anhydrous sodium sulfate as a stabilizer, stir at 70°C for 24 hours, filter and wash with distilled water, then dry at 60°C for 4 hours, grind and calcine at 400°C for 3.5 hours to obtain Zr-Ce-TiO2 / attapulgite composite catalyst; The weight ratio of the attapulgite, tetrabutyl titanate, cerium nitrate, ethanol, sulfuric acid solution, zirconium hydroxide solution and anhydrous sodium sulfate is 20:5:2:50:10:10:2; (2) Mix citric acid, n-octanol, a catalyst and cyclohexane, heat under reflux at a reaction temperature of 175°C for 2 hours until the acid value no longer changes. After the reaction is completed, cool naturally, wash four times with a 4% by volume aqueous solution of sodium carbonate at 70°C, separate the liquids, and dealcoholize under reduced pressure to obtain the product.
[0032] Wherein, the weight ratio of the citric acid, n-octanol, catalyst and cyclohexane is 6:14:0.2:12.
[0033] The acid value before and after the esterification reaction was measured according to the GB1668-95 method. In this embodiment, the esterification rate was 99.0%. After the catalyst was reused 4 times, the esterification rate could still be maintained at 98.4%.
[0034] Comparative Example 1 This comparative example provides a preparation process of trioctyl citrate plasticizer, the steps comprising: (1) Preparation of catalyst: Take attapulgite with an average particle size of 250 mesh and disperse it in an ethanol solution of cerium nitrate, add a sulfuric acid solution with a concentration of 0.75 mol / L and a saturated aqueous solution of zirconium hydroxide, and add anhydrous sodium sulfate as a stabilizer, stir at 75°C for 22 hours, filter, wash with distilled water, and then dry at 65°C for 3.5 hours. After grinding, calcine at 460°C for 4 hours to obtain a Zr-Ce / attapulgite composite catalyst; The weight ratio of the attapulgite, cerium nitrate, ethanol, sulfuric acid solution, zirconium hydroxide solution and anhydrous sodium sulfate is 25:1.5:60:9:12.5:1.5; (2) Mix citric acid, n-octanol, a catalyst and cyclohexane, heat and reflux for reaction at a temperature of 173°C for 2.5 hours until the acid value no longer changes. After the reaction is completed, cool naturally and wash three times with a 4% by volume aqueous solution of sodium carbonate at 75°C. Separate the liquids and dealcoholize under reduced pressure to obtain the product.
[0035] Wherein, the weight ratio of the citric acid, n-octanol, catalyst and cyclohexane is 7:13:0.15:13.
[0036] The acid value before and after the esterification reaction was measured according to the method of GB1668-95. In this embodiment, the esterification rate was 95.8%. After the catalyst was reused 4 times, the esterification rate could still be maintained at 92.6%.
[0037] Comparative Example 2 This comparative example provides a preparation process of trioctyl citrate plasticizer, the steps comprising: (1) Preparation of catalyst: Take attapulgite with an average particle size of 250 mesh and disperse it in an ethanol solution of tetrabutyl titanate, add a sulfuric acid solution with a concentration of 0.75 mol / L and a saturated aqueous solution of zirconium hydroxide, and add anhydrous sodium sulfate as a stabilizer, stir at 75°C for 22 hours, filter, wash with distilled water, and then dry at 65°C for 3.5 hours. After grinding, calcine at 460°C for 4 hours to obtain a Zr-TiO2 / attapulgite composite catalyst; The weight ratio of the attapulgite, tetrabutyl titanate, ethanol, sulfuric acid solution, zirconium hydroxide solution and anhydrous sodium sulfate is 25:6:60:9:12.5:1.5; (2) Mix citric acid, n-octanol, a catalyst and cyclohexane, heat and reflux for reaction at a temperature of 173°C for 2.5 hours until the acid value no longer changes. After the reaction is completed, cool naturally and wash three times with a 4% by volume aqueous solution of sodium carbonate at 75°C. Separate the liquids and dealcoholize under reduced pressure to obtain the product.
[0038] Wherein, the weight ratio of the citric acid, n-octanol, catalyst and cyclohexane is 7:13:0.15:13.
[0039] The acid value before and after the esterification reaction was measured according to the method of GB1668-95. In this embodiment, the esterification rate was 95.2%. After the catalyst was reused for 4 times, the esterification rate could still be maintained at 91.2%.
[0040] Comparative Example 3 This comparative example provides a preparation process of trioctyl citrate plasticizer, the steps comprising: (1) Preparation of catalyst: Take attapulgite with an average particle size of 250 mesh and disperse it in an ethanol solution. Then, add a sulfuric acid solution with a concentration of 0.75 mol / L and a saturated aqueous solution of zirconium hydroxide, and add anhydrous sodium sulfate as a stabilizer. Stir at 75°C for 22 h, filter, wash with distilled water, and then dry at 65°C for 3.5 h. After grinding, calcine at 460°C for 4 h to obtain a Zr / attapulgite composite catalyst. The weight ratio of the attapulgite, ethanol, sulfuric acid solution, zirconium hydroxide solution and anhydrous sodium sulfate is 25:60:9:12.5:1.5; (2) Mix citric acid, n-octanol, a catalyst and cyclohexane, heat and reflux for reaction at a temperature of 173°C for 2.5 hours until the acid value no longer changes. After the reaction is completed, cool naturally and wash three times with a 4% by volume aqueous solution of sodium carbonate at 75°C. Separate the liquids and dealcoholize under reduced pressure to obtain the product.
[0041] Wherein, the weight ratio of the citric acid, n-octanol, catalyst and cyclohexane is 7:13:0.15:13.
[0042] The acid value before and after the esterification reaction was measured according to the GB1668-95 method. In this embodiment, the esterification rate was 94.6%. After the catalyst was reused 4 times, the esterification rate could still be maintained at 90.3%.
[0043] Comparative Example 4 This comparative example provides a preparation process of trioctyl citrate plasticizer, the steps comprising: (1) Preparation of catalyst: Take an ethanol solution of tetrabutyl titanate and cerium nitrate, add a 0.75 mol / L sulfuric acid solution and a saturated aqueous solution of zirconium hydroxide, and add anhydrous sodium sulfate as a stabilizer, stir at 75°C for 22 hours, filter, wash with distilled water, and then dry at 65°C for 3.5 hours. After grinding, calcine at 460°C for 4 hours to obtain Zr-Ce-TiO2 catalyst; The weight ratio of tetrabutyl titanate, cerium nitrate, ethanol, sulfuric acid solution, zirconium hydroxide solution and anhydrous sodium sulfate is 25:6:1.5:60:9:12.5:1.5; (2) Mix citric acid, n-octanol, a catalyst and cyclohexane, heat and reflux for reaction at a temperature of 173°C for 2.5 hours until the acid value no longer changes. After the reaction is completed, cool naturally and wash three times with a 4% by volume aqueous solution of sodium carbonate at 75°C. Separate the liquids and dealcoholize under reduced pressure to obtain the product.
[0044] Wherein, the weight ratio of the citric acid, n-octanol, catalyst and cyclohexane is 7:13:0.15:13.
[0045] The acid value before and after the esterification reaction was measured according to the method of GB1668-95. In this embodiment, the esterification rate was 91.2%. After the catalyst was reused 4 times, the esterification rate could still be maintained at 84.2%.
[0046] Comparative Example 5 This comparative example provides a preparation process of trioctyl citrate plasticizer, the steps comprising: (1) Preparation of catalyst: Take attapulgite with an average particle size of 250 mesh and disperse it in an ethanol solution of tetrabutyl titanate, add a sulfuric acid solution with a concentration of 0.75 mol / L, and add anhydrous sodium sulfate as a stabilizer, stir at 75°C for 22 hours, filter, wash with distilled water, and then dry at 65°C for 3.5 hours. After grinding, calcine at 460°C for 4 hours to obtain a TiO2 / attapulgite composite catalyst; The weight ratio of the attapulgite, tetrabutyl titanate, ethanol, sulfuric acid solution and anhydrous sodium sulfate is 25:6:1.5:60:9:12.5:1.5; (2) Mix citric acid, n-octanol, a catalyst and cyclohexane, heat and reflux for reaction at a temperature of 173°C for 2.5 hours until the acid value no longer changes. After the reaction is completed, cool naturally and wash three times with a 4% by volume aqueous solution of sodium carbonate at 75°C. Separate the liquids and dealcoholize under reduced pressure to obtain the product.
[0047] Wherein, the weight ratio of the citric acid, n-octanol, catalyst and cyclohexane is 7:13:0.15:13.
[0048] The acid value before and after the esterification reaction was measured according to the GB1668-95 method. In this embodiment, the esterification rate was 90.4%. After the catalyst was reused 4 times, the esterification rate could still be maintained at 83.5%.
[0049] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the present invention.
Claims
1. A process for preparing trioctyl citrate plasticizer, characterized in that: The steps include: (1) Preparation of catalyst: Disperse attapulgite in an ethanol solution of tetrabutyl titanate and cerium nitrate, add sulfuric acid solution and zirconium hydroxide solution dropwise thereto, and add anhydrous sodium sulfate as a stabilizer, stir at 70-80°C for 20-24h, filter and wash with distilled water, then dry at 60-70°C for 3-4h, grind into powder, and calcine at 400-500°C for 3.5-4.5h to obtain a Zr-Ce-TiO2 / attapulgite composite catalyst; (2) Mix citric acid, n-octanol, a catalyst and cyclohexane, heat and reflux to react until the acid value no longer changes, cool naturally after the reaction, wash, separate the liquids, and dealcoholize under reduced pressure to obtain the product; The weight ratio of the attapulgite, tetrabutyl titanate, cerium nitrate, ethanol, sulfuric acid solution, zirconium hydroxide solution and anhydrous sodium sulfate is (20-30): (5-8): (1-2): (50-70): (8-10): (10-15): (1-2); The weight ratio of the citric acid, n-octanol, catalyst and cyclohexane is (6-8): (12-14): (0.1-0.2): (12-14).
2. The preparation process of a trioctyl citrate plasticizer according to claim 1, characterized in that: The average particle size of the attapulgite is 200-300 meshes.
3. The preparation process of a trioctyl citrate plasticizer according to claim 1, characterized in that: The concentration of the sulfuric acid solution is 0.5-1 mol / L.
4. The preparation process of a trioctyl citrate plasticizer according to claim 1, characterized in that: The zirconium hydroxide solution is a saturated aqueous solution of zirconium hydroxide.
5. The preparation process of a trioctyl citrate plasticizer according to claim 1, characterized in that: The temperature of the heating reflux reaction is 170-175° C., and the reaction time is 2-3 hours.
6. The preparation process of a trioctyl citrate plasticizer according to claim 1, characterized in that: The washing is performed by using a 4% by volume sodium carbonate aqueous solution at 70-80° C. for 3-4 times.
7. A trioctyl citrate plasticizer prepared by the preparation process of the trioctyl citrate plasticizer according to any one of claims 1 to 6.
8. Use of the trioctyl citrate plasticizer as claimed in claim 7 in plastic additives.
Citation Information
Patent Citations
Method for synthesizing trioctyl lemon acid
CN101245008A
Method for synthesizing triester citrate with hydrophobic solid acid as catalyst
CN101270045A
Method for preparing tributyl citrate by using rare-earth salt binary complex type solid acid as catalyst
CN101391957A
Method for producing plasticizer tirbutyl citrate
CN101735055A
Method for synthesizing citric acid ester type compound
CN101830803A